Assessment of nutritional status of elderly population living at high altitude regions of India utilizing Mini Nutritional Assessment (MNA) methodology - Gupta, Aakriti; Kapil, Umesh; Belwal, Ravi (Indian Journal of Community Health, 2022)
Background: Malnutrition is associated with increased risk of morbidity and mortality amongst elderly population. There is lack of scientific evidence on the staus of malnutrition amongst elderly population residing at high altitude regions of Uttarakhand, India. Background: Malnutrition is associated with increased risk of morbidity and mortality amongst elderly population. Lack of scientific evidence exists on the status of malnutrition amongst elderly population residing at high altitude regions of Uttarakhand, India. Materials and methods: A community based cross-sectional study was conducted in high altitude regions of District Nainital. A total of 980 elderly subjects were selected from 30 clusters identified using population proportionate to size sampling method. Nutritional status of the elderly population was assessed using Mini Nutritional Assessment (MNA) tool. Data was entered in MS Excel 2007 and analyzed using SPSS version 20.0. Results: The results of MNA revealed that 14.3% of the elderly subjects were malnourished. High prevalence of malnutrition was found among subjects who were illiterate (74.5%), financially dependent (75.2%), belonged to low monthly income (43.3%) had poor appetite (71.6%) and chewing problems (63.1%); (p<0.0001). Conclusions: High prevalence of malnutrition was present amongst the elderly population in India. There is a need for timely assessment of malnutrition for maintenance of nutritional status and prevention of chronic diseases. Materials and methods: A community based cross-sectional study was conducted in high altitude regions of District Nainital. A total of 980 elderly subjects were selected from 30 clusters identified using population proportionate to size sampling method. Nutritional status of the elderly population was assessed using Mini Nutritional Assessment (MNA) tool. Data was entered in MS Excel 2007 and analyzed using SPSS version 20.0. Results: The results of MNA revealed that 14.3% of the elderly subjects were malnourished. High prevalence of malnutrition was found among subjects who were illiterate (74.5%), financially dependent (75.2%), belonged to low monthly income (43.3%) had poor appetite (71.6%) and chewing problems (63.1%); (p<0.0001). Conclusions: High prevalence of malnutrition was present amongst the elderly population in India. There is a need for timely assessment of malnutrition for maintenance of nutritional status and prevention of chronic diseases.